Penelitian makna imbuhan pen- dalam Bahasa Melayu: satu kajian rangka rujuk silang - Nor Hashimah Jalaluddin; Ahmad Harith Syah (Penerbitan UKM, 2009)
Many Malay grammarians describe the semantic of peN- based on its structure and functions. Za’ba (1965), Asmah (1993), Nik Safiah et al. (1993), Abdullah and Liaw (1994) and few others agreed that the prefix peN- semantically refers to as an agent and instrument. Some grammarians noted that the prefix peN- as a patient, habitual manner and abstract marker. For instance, petani (farmer) is an agent, perokok (smoker) is habitual, pemarah (bad tempered) is an abstract, penimbang (scale) is a measurement and so on. It is apparent that the description on peN- seems to be quite broad and overlapping and this can lead to ambiguity in meaning. Based on 5 million DBP-UKM data bank, peN and its concordance are extracted for analysis. Relevance theory that focuses on communication and cognition with reference assignment as one of its traits can offer a better description on peN-. In reference assignment, bridging cross reference (BCR) which allows the dependent on context in utterances facilitate the hearer to determine the intended meaning. ‘Pemakan sayur’ (vegetarian) and ‘perosak bahasa’ (language corrupter) need no modifier to determine that they are referring to human, as opposed to ‘burung pemakan bangkai’ - (carnivorous bird) and serangga perosak (destructive insects). The latter needs a modifier such as ‘burung’ (bird) and ‘serangga’ (insect) to show that it is non-human. In sum, with BCR we are able to differenciate the prefix peNeither referring to human and non human based on context and attributes